Efektivitas Jar Positive Self-Talk Therapy terhadap Remaja dengan Perilaku Self-Injury di SMP Telkom Purwokerto - Safira Jihan Safitri; Suci Ratna Estria (Universitas Malahayati Lampung, 2025)
ABSTRACT Self-injury is a serious issue involving intentional physical harm without the intent to end one's life and is not considered a socially or medically acceptable procedure. The prevalence of self-injury among adolescents has significantly increased over the past decade. According to a YouGov Omnibus report (2019), more than one-third (36%) of Indonesians have intentionally engaged in self-injury, with 45% of respondents being adolescents. Further, recent research by Faradiba (2021) revealed that 20.21% of Indonesian adolescents have been involved in self-injury behavior. A preliminary study conducted by the researchers on July 22, 2024, at Telkom Junior High School Purwokerto discovered that 81 participants had engaged in self-injury, while 110 participants had considered engaging in self-injury. This study aimed to identify the effectiveness of jar positive self-talk therapy in adolescents with self-injury behavior at SMP Telkom Purwokerto. This research employed a pre-experimental design with a one-group pre-test and post-test approach. The sampling technique used was total sampling, with a total of 81 respondents. The research instrument utilized was the Non-Suicidal Self-Injury Expectancy Questionnaire (NEQ). The findings indicated that the average expectancy score for self-injury behavior before the intervention with jar positive self-talk therapy was 70.80, which decreased to 52.83 after the intervention. The Paired Sample T-test yielded a p-value of 0.000, with an effect size (r) of 0.79. This study concludes that jar positive self-talk therapy is effective in addressing self-injury behavior among adolescents at SMP Telkom Purwokerto. Keywords: Self-injury, Adolescents, Jar Positive Self-Talk Therapy. ABSTRAK Self-injury merupakan masalah serius, perilaku ini dapat menyebabkan kerusakan fisik yang disengaja meskipun tanpa niat untuk mengakhiri hidup dan bukan merupakan prosedur yang dianggap legal menurut sosial maupun medis. Self-injury pada remaja prevalensinya semakin meningkat dalam satu dekade terakhir. YouGov Omnibus (2019) melaporkan lebih dari sepertiga (36%) orang Indonesia pernah dengan sengaja melakukan self-injury, dengan 45% responden berada pada usia remaja. Selain itu, data terbaru dari penelitian Faradiba (2021) menunjukan bahwa 20,21% remaja di Indonesia pernah terlibat dalam perilaku self-injury. Studi pendahuluan yang telah dilakukan oleh peneliti pada tanggal 22 Juli 2024 di SMP Telkom Purwokerto didapatkan hasil bahwa 81 peserta pernah melakukan tindakan self-injury dan 110 peserta pernah berpikiran untuk melakukan self-injury. Penelitian ini bertujuan untuk mengidentifikasi efektivitas jar positive self-talk therapy terhadap remaja dengan perilaku self-injury di SMP Telkom Purwokerto.Desain penelitian ini adalah pre-experimental dengan one group pre-post test design. Teknik pengambilan sampel menggunakan total sampling dengan jumlah total responden adalah 81 responden. Instrumen penelitian menggunakankuisioner The Non-Suicidal Self-Injury Expectancy Questionnaire (NEQ). Hasil penelitian ini menunjukan bahwa rata-rata skor ekspektansi perilaku self-injury sebelum intervensi dengan media jar positive self-talk therapy adalah 70.80 dan setelah dilakukan intervensi menjadi 52.83. Hasil Uji Paired Sample T-test p-value 0,000 dan hasil effect size r = 0,79. Penelitian ini menyimpulkan terdapat efektivitas jar positive self-talk therapy terhadap remaja dengan perilaku self-injury di SMP Telkom Purwokerto. Kata Kunci: Self-injury, Remaja, Jar Positive Self-Talk Therapy.